The influence of earnings management and asymmetry information on the cost of equity capital moderated by disclosure level - Kiswanto, Kiswanto; Fitriani, Novi (Jurnal Keuangan dan Perbankan, 2019)
Company value can be increased by minimizing the cost of equity capital. The cost of equity capital is the rate of return required by investors in accordance with company condition. The purpose of this study was to analyze the influence of earning management and asymmetry information on the cost of equity capital with disclosure level as the moderating variable by presenting Company Size, Market Capitalization, Leverage, and Profitability as the control variables. The population of the study was 148 manufacturing companies listed on the Indonesia Stock Exchange with the total unit of analysis was 330.Â  Then, hypotheses were analyzed with software Eviews 9. The results of the study showed that earning management, asymmetry information, company size, profitability, and disclosure level had significant influences on the cost of equity capital for both large and small companies. Then, it also showed that disclosure level was able to moderate the influence of earning management on the cost of equity capital, but it was not able to moderate the influence of asymmetry information on the cost of equity capital both large and small companies. It was interesting because the coefficients of influence were different based on the company size. On small companies, the influence of disclosure level on asymmetry information was negative.JEL Classification: D82, G310DOI:Â https://doi.org/10.26905/jkdp.v23i1.1926